Morphological Variations in Jack Pine (Pinus Banksiana) Along its' Central to Northern Population Ranges - Kellman, Lisa Marie (My University, 1989)
The analysis of six jack pine populations along a north-south transect through the MacKenzie River Valley in the Northwest Territories revealed no significant latitudinal trends in cone and seed morphometric measurements. In attempting to determine whether any variations may be environmentally induced, Radial Growth Rates were, 1)compared between sites. and 2), were correlated with morphometric measurements. No significant results were produced. In correlating trait measurements between sites and between one another in order to determine whether migration may be producing trends, again no significant relatlonships were obtained. A comparison of jack pine with the similar species lodgepole pine suggests that if the same factors controlling the migration of lodgepole pine also control jack pine migration, wing loading should be less in more recent populations. However, this study indicates no significant results in this respect. It is suggested, however, that a further sampling south along the latitudinal transect may produce significant results.
Keywords: morphological, population, jack pine, Mackenzie River, latitudinal, transect